2007
DOI: 10.1038/sj.clpt.6100380
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pharmacokinetic Basis for Zolpidem Dosing in Children With Sleep Difficulties

Abstract: The pharmacokinetics of zolpidem was assessed in this open-label, dose-escalation study in children with insomnia. Twenty-one children, seven per age group (2-6, >6 to 12, >12 to 18 years), received a single dose of zolpidem at one of the three dose levels (0.125, 0.25, or 0.50 mg/kg (20 mg maximum dose)). Multiple pharmacokinetic measures were assessed at nine post-dose intervals and pharmacodynamics was assessed by polysomnography and actigraphy. Significant pharmacokinetic effects by dose were observed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Zolpidem (brand name Ambien) is an imidazopyridine agent that is an agonist to the benzodiazepine receptor component of the γ‐aminobutyric acid A receptor complex which is commonly used as a hypnotic/sedative agent . It has a very rapid onset of action, can be orally administered, and is rapidly metabolized and eliminated . Additionally, one study has demonstrated utility of zolpidem as oral premedication in adults prior to general anesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…Zolpidem (brand name Ambien) is an imidazopyridine agent that is an agonist to the benzodiazepine receptor component of the γ‐aminobutyric acid A receptor complex which is commonly used as a hypnotic/sedative agent . It has a very rapid onset of action, can be orally administered, and is rapidly metabolized and eliminated . Additionally, one study has demonstrated utility of zolpidem as oral premedication in adults prior to general anesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…23 The only other pediatric zolpidem pharmacokinetic study was conducted by Blumer et al, 24 which used a single dose escalation design to evaluate 3 zolpidem dosage regimens (0.125, 0.25, and 0.5 mg/kg) among otherwise healthy children with insomnia. 23 The only other pediatric zolpidem pharmacokinetic study was conducted by Blumer et al, 24 which used a single dose escalation design to evaluate 3 zolpidem dosage regimens (0.125, 0.25, and 0.5 mg/kg) among otherwise healthy children with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…In the previously mentioned study conducted by Blumer et al, 24 the pharmacokinetics of zolpidem were evaluated among otherwise healthy children suffering from insomnia. Age was found to significantly influence the zolpidem area under the concentration-time curve, half-life, and mean residence time.…”
Section: Discussionmentioning
confidence: 99%
“…These medications only have FDA approval for use in patients older than 18 years old, and therefore, the use of these medications in children is considered Boff-label.^They may also be difficult to administer in children as none of these medications are offered in liquid or dissolvable wafer form [26]. There are reports of zolpidem abuse among adolescents [27,28].…”
Section: Benzodiazepinesmentioning
confidence: 99%